Occurrence of two non-ubiquitous plant defense strategies : production of extrafloral nectaries and volatile organic compounds - Alona C. Linatoc (2009)
Plants synthesize numerous classes of natural products that accumulate during its development and are thought to function as constitutive and/or facultative defense against herbivores and pathogens, and in certain cases, defense mechanisms against various extreme environmental conditions. This study looked into the occurrence of two carbon-based defense strategies in plants, namely, production of extrafloral nectaries and emission of phytogenic volatile organic compounds. The first part of the thesis consolidated studies done worldwide on plants’ ability to produce extrafloral nectaries and emit volatile organic compounds. All studies on EFNs and VOCs were so far done independently of each other, hence after crosschecking all VOC-emitting and EFN-bearing plants (1,293 species combined), only 45 species were found to exhibit both defense strategies. The comprehensive list of EFN-bearing and VOC-emitting species worldwide is presented as Appendices C and D, respectively. The second part of this study took a closer look at tropical plants’ ability to produce these two common, yet non-ubiquitous carbon-based defense strategies. A survey of 165 species was conducted in Danum Valley, Sabah, Malaysia. Results showed that 78% (129 species) of the species surveyed were emitting volatile organic compounds, while only 25% (41 species) were found to produce extrafloral nectaries. Thirty three (33) species were observed to exhibit EFN glands and emit PVOCs. Incidentally, all 12 dipterocarp species were VOC emitters, while 9 were EFN-bearing plants. In terms of plant habit and successional stages, VOC emission was common in all screened plant habits (i.e. trees, shrubs, herb, grass, palm, and climbers) while EFN were observed to occur in all plant habits except in palms and climbers. Finally, it was observed that EFN and VOC productions are both common occurrence in climax and pioneer species.